Reasoning web : web logic rules : 11th International Summer School 2015, Berlin, Germany, July 31- August 4, 2015, tutorial lectures /: web logic rules : 11th International Summer School 2015, Berlin, Germany, July 31- August 4, 2015, tutorial lectures. (2015) - Unknown
No abstract available